Figurative Speech In Calum Scott's Song “You Are The Reason” - Poluan, Feibi; Liando, Nihta V. F; Mamentu, Agustine C. (Program Studi Pendidikan Bahasa Inggris, 2025)
Figure of speech is an expression used for literacy needs both verbally and in writing. This study aims to identify the types of figurative speech and analyze the meaning of figurative speech found in the song lyric